A novel AMPK activator improves hepatic lipid metabolism and leukocyte trafficking in experimental hepatic steatosis - Xueying Peng; Jin Li; Minjie Wang; Kai Qu; Haibo Zhu (Elsevier, 2019)
A novel AMP-activated protein kinase (AMPK) activator, IMM-H007 (H007), has been reported to reduce serum lipid levels and inhibit lipid accumulation in the liver in hyperlipidemic animal models. However, how H007 ameliorates hepatic steatosis and inflammation remains unknown. In the present study, H007, at 200 mg/kg, reduced hepatic lipid levels and the levels of collagenous fiber in the liver in high-fat diet (HFD)-fed hamsters compared to those in the HFD group. Meanwhile, compared to the controls, H007 significantly inhibited sterol-regulatory element binding protein (SREBP)-1c and acetyl CoA carboxylase (ACC) expression by upregulating the AMPK activity, suppressing the saturated fatty acid accumulation and increasing polyunsaturated fatty acid synthesis in the liver. Compared to the controls, H007 treatment inhibited the expression of monocyte chemotactic protein (MCP-1) in fatty acid-treated HepG2 cells; suppressed leukocyte adherence and rolling on the liver microvasculature; and suppressed hepatic macrophage infiltration. H007 also suppressed the expression of nuclear factor-κB (NF-κB) p65 in fatty acid- and lipopolysaccharide-treated HepG2 cells compared to that in the controls by activating AMPK. These data suggested that H007 had a beneficial effect by improving the lipid composition in the liver and inhibiting inflammatory cell trafficking in the development of nonalcoholic fatty liver disease. Keywords: AMPK activator, Hepatic lipid metabolism, Leukocyte trafficking, Hepatic steatosis, Inflammation